1996
DOI: 10.1093/ajcn/64.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Fat distribution and cardiovascular risk factors in obese adolescent girls: importance of the intraabdominal fat depot

Abstract: The regional distribution of body fat has repeatedly been found to be a significant and independent risk factor for cardiovascular disease in both obese men and women. To determine whether abnormalities in the lipid-lipoprotein profile and systolic and diastolic blood pressure are related to specific fat depots early in the course of obesity, we used magnetic resonance imaging to measure accurately intraabdominal and subcutaneous fat masses in 14 obese [body mass index (BMI; in kg/m2) 30 +/- 1.3] and 10 nonobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
142
2
8

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(165 citation statements)
references
References 24 publications
13
142
2
8
Order By: Relevance
“…04) related to both total cholesterol and LDL-cholesterol, and triacylglycerol levels (Brambilla et al 1994). A separate study in obese adolescent girls has shown that cardiovascular risk factors including plasma triacylglycerol and HDL-cholesterol concentrations and systolic and diastolic blood pressure are directly related to the amount of intra-abdominal fat (Caprio et al 1996). Similar findings have also been reported for obese children aged 7-11 years (Owens et al 1998).…”
supporting
confidence: 65%
“…04) related to both total cholesterol and LDL-cholesterol, and triacylglycerol levels (Brambilla et al 1994). A separate study in obese adolescent girls has shown that cardiovascular risk factors including plasma triacylglycerol and HDL-cholesterol concentrations and systolic and diastolic blood pressure are directly related to the amount of intra-abdominal fat (Caprio et al 1996). Similar findings have also been reported for obese children aged 7-11 years (Owens et al 1998).…”
supporting
confidence: 65%
“…Indeed (as in adults), central adiposity in children has been related to risk factors for cardiovascular disease and type II diabetes mellitus, including increased blood pressure, an adverse blood lipid profile and raised fasting insulin levels. [11][12][13][14][15][16] Increases in waist circumference will reflect both increases in visceral adiposity and increases in centrally located subcutaneous fat, both of which are associated with a number of adverse metabolic outcomes. This is of concern, as it has recently been shown in British youth aged 11-16 y that central adiposity, as measured by the waist circumference, has increased at a far greater rate than overall fatness (indicated by the BMI) over the past 10-20 y.…”
Section: Introductionmentioning
confidence: 99%
“…In children, it has been also shown a signi®cant relation between adipose tissue distribution and some metabolic complications of obesity (Legido et al, 1989;Caprio S et al, 1996;Gower et al, 1998;van Lenthe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%